PSIKOLOGI PENDIDIKAN DAN ILMU MENGAJAR - Muhammad Ichsan (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
Educational psychology is the science of knowledge-that talks about human behavior in the teaching-learning process, and he has a close relationship with science teaching. Where in the process of teaching, educators are required to have adequate knowledge of the material being taught, and also mastered the different methods of delivery so that what is delivered is understandable and easily understood by students. So mastery of educational psychology (educational psychology) is a demand for educators. As defined educational psychology is simply a science which studies human behavior that takes place in the teaching-learning process. While teaching is defined as an activity to organize or manage the environment as well as possible and connect with the child, resulting in a process of learning. In the teaching-learning process, educators should pay attention to the students, the rate of growth and the individual differences that exist between them. As the experts in this case the pupils to classify three types: (1) Type of auditory, easy to accept the lesson by hearing. (2) Type Visual, easy merima learning through sight. (3) Type of methodical, easy to accept the lesson through the motions.